Defiance of Convention: A Silent Repulsion on Patriarchal Decree for self-empowering in The Lowland - Nepal, Khagendra Prasad (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2025)
This paper seeks to analyze Jhumpa Lahiri’s defiance of convention with particular reference to the main female characters Gauri and Bela of the novel through their self-empowering. This study shows how the female characters develop their sense of defiance through their action and behavior more than their words, and how they empower themselves in course of their life proving their potentials. The role of a mother in context of Gauri and the meaning of mother in regards of Bela goes on changing when they begin to denounce the conventional practices of the related spheres. The similar types of instances are the focusing concerns of this study. It uses qualitative methodology and takes existential feminism as a theoretical tool to interpret and analyze the primary texts. Instead of focusing on the analysis of the theme of the text, the article focuses on analysis of the text in concern with female characters’ relation, practices and notions on the existing social beliefs and traditions particularly in women relation. The paper discusses how the personality of Gauri and Bela get changes across the novel based on identity transformation. This study argues that these female characters challenge the existing conventions only when they come to feel self-empowered. It also makes an important point to make women empowerment a cursory discourse for the change in many social constraints imposed by patriarchal belief system.